Effect of Concurrent Co-Morbidity in the Management of Musculoskeletal Disorders - Olanrewaju, Saliu Akeem; O. Omoyemi, Ogwumike; Gbonjubola, Yusuff Tunde; Gordons, Alexander E. (Journal of Pharmacy Practice and Community Medicine)
Musculoskeletal disorders exert a substantial impact on the quality of life of affected individuals as well as placing a major economic burden on work organizations and society in terms of compensation costs in the short term and lost wages in the long-term. Musculoskeletal conditions may occur with or without concurrent chronic conditions, which may affect the effectiveness of physiotherapy management. The impact of co-existing co-morbidities other than the primary diseases the patient is being managed for, on the treatment, and on the outcomes of physiotherapy programs for individual patient cannot be overemphasized. Hence, the purpose of this review was to summarize the management of musculoskeletal disorders and the impact of chronic conditions on their treatment outcome.
Keywords: Musculoskeletal disorder; Comorbidity; Risk factors; Manual therapy; Electrotherapy